Quantum dots: The ultimate down-conversion material for LCD displays - Steckel, Jonathan S.; Ho, John; Hamilton, Charles; Xi, Jingqun; Breen, Craig; Liu, Wenhao; Allen, Peter; Coe-Sullivan, Seth (Journal of the Society for Information Display, 2015)
Assuming that large color gamut and therefore better color reproducibility will be a highly desired feature of all displays as we look to the near future, we make the case in this paper that quantum dots (QDs) are currently the down‐conversion technology of choice that will allow liquid crystal display makers to cost‐effectively reach and exceed 100% of the NTSC (National Television Standard Committee) and Adobe RGB color standards while achieving maximum system efficiency. We will discuss in detail the numerous fundamental advantages of QDs over phosphors, along with their scientific origins, and make the case that QDs are the ultimate light generating material for next‐generation displays. Quantum dots (QDs) are currently the light‐conversion technology of choice for achieving outstanding color reproducibility, allowing display makers to cost‐effectively exceed the NTSC (National Television Standard Committee) and Adobe RGB color standards while achieving maximum system efficiency. The numerous fundamental advantages of QDs over phosphors, along with their scientific origins are discussed, and the case is made that QDs are the ultimate light‐generating material for next‐generation displays.